The effects of jujube (Ziziphus jujube) on metabolic and mental health outcomes in patients with metabolic syndrome: A randomized controlled trial - Karim Parastouei; Saad Badai Nashtar; Zaid Al-Attar; Parivash Shekarchizadeh-Esfahani; Gholamreza Askari (Elsevier, 2024)
Objectives: The effects of jujube (Ziziphus jujube) consumption on metabolic and mental health outcomes in subjects diagnosed with metabolic syndrome (MetS) is unknown and remains to be examined. Hence, we carried out a parallel-group, randomized controlled trial to investigate this issue. Methods: Eligible participants were randomly assigned to the intervention (n = 30) or the control (n = 30) groups to receive either jujube or a placebo for eight weeks. Subjects were provided with 30 g dried jujube powder or placebo and were asked to consume half of the powder at 10 a.m. and the rest at 4 p.m. Lipid profile, fasting blood glucose (FBG), waist circumference (WC), and blood pressure were evaluated as primary outcomes. Secondary outcomes collected were mental health measures (e.g., depression, anxiety, and stress). Results: Jujube consumption failed to decrease FBG, total cholesterol, low-density lipoprotein cholesterol, and blood pressure, as well as depression and anxiety scores (P > 0.05). However, the between-group comparison revealed a significant improvement in WC (− 3.98 vs. − 0.51, P = 0.01), triglyceride (TG) (− 24.96 vs. − 0.73, P = 0.03), and high-density lipoprotein cholesterol (HDL-C) (2.83 vs. 0.40, P = 0.01) in the jujube group compared to the placebo. In addition, compared to the control group, jujube consumption led to a significant improvement in the score of stress (− 5.80 vs. − 2.86, P = 0.01). Conclusion: Jujube consumption only had beneficial effects on WC, TG, and HDL-C in subjects with MetS. However, the current study has methodological weaknesses in blinding and herb purity/potency testing, which should be addressed in future studies.